2022
DOI: 10.1021/acsami.1c23637
|View full text |Cite
|
Sign up to set email alerts
|

Black Phase of Inorganic Perovskite Stabilized with Carboxyimidazolium Iodide for Stable and Efficient Inverted Perovskite Solar Cells

Abstract: As all-inorganic perovskite (CsPbI3–x Br x ) is prone to phase transition from the α phase (black phase) to the δ phase (yellow phase) in a humid environment or under heating, improving the phase stability of all-inorganic perovskite of the black phase is one of the urgent problems to solve. Herein, 1,2-dimethyl-3-acetylimidazolium iodide (DMAII) is spin-coated onto the surface of CsPbI3–x Br x perovskite for use in p–i–n perovskite solar cells (PSCs). We find that the DMAII coating has two effects on the CsP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…This spectral change could be ascribed to the coordination interactions between C–N and Pb 2+ . 46,48 In addition, the stretching vibration peak of the C–F bond located at about 1230 cm −1 shifted to lower wavenumber in the fluorinated organic ammonium halide salts/lead halides complex samples, indicating the reinforced interaction, which is also expected to passivate Pb 2+ defects. 39,49 Based on the above results, we concluded that the amino group and C–F bond could connect molecules to the Pb–X framework by coordinating with the under-coordinated Pb 2+ or hydrogen bonding with the halogen ions and finally passivated CsPbI 2 Br defects.…”
Section: Resultsmentioning
confidence: 96%
“…This spectral change could be ascribed to the coordination interactions between C–N and Pb 2+ . 46,48 In addition, the stretching vibration peak of the C–F bond located at about 1230 cm −1 shifted to lower wavenumber in the fluorinated organic ammonium halide salts/lead halides complex samples, indicating the reinforced interaction, which is also expected to passivate Pb 2+ defects. 39,49 Based on the above results, we concluded that the amino group and C–F bond could connect molecules to the Pb–X framework by coordinating with the under-coordinated Pb 2+ or hydrogen bonding with the halogen ions and finally passivated CsPbI 2 Br defects.…”
Section: Resultsmentioning
confidence: 96%
“…254,259 The stabilization of the desired bulk α-CsPbI 3 phase is only achieved at high temperatures (>150 °C), [260][261][262] and this material is prone to oxygen and moisture degradation, which can be attributed to its low tolerance fact or (0.803). 263 For that reason, it is quite hard to obtain long-term stability in bulk CsPbI 3 -based solar cells, and the exposure of the unencapsulated device to ambient air results in the irreversible formation of the yellow non-photoactive phase. 264,265 On the other hand, PSCs prepared using CsPbI 3 NCs (E g ∼ 1.72 eV, excellent for top-cell in tandem solar cells), are not only more stable under ambient conditions compared to the bulk analog, but also allow stabilization of the photoactive phase at room temperature.…”
Section: Perovskite Nanocrystals Vs Bulk Perovskitesmentioning
confidence: 99%
“…DMAII provides electrons to the Pb 2+ ions to form coordination bonds, and the binding energy of electrons was thus reduced, which served to passivate the surface defects and achieved the best PCE of 13.14% for the inverted PSCs structure. [94] Du et al prepared CsPbI 3 thin films containing low concentration of a novel ionic liquid EMIMHSO 4 , which successfully reduced the perovskite grain boundaries, strongly coordinated with the under-coordinated Pb 2+ to passivate iodide vacancy defects. The results showed that the PCE of CsPbI 3 solar cells was as high as 20.01%.…”
Section: Passivation By Lewis Basementioning
confidence: 99%